Measuring the quality of motivational interviewing in primary health care encounters: The development and validation of the motivational interviewing assessment scale (MIAS). (2nd July 2016) - Campiñez Navarro, Manuel; Pérula de Torres, Luis Ángel; Bosch Fontcuberta, Josep M.; Barragán Brun, Nieves; Arbonies Ortiz, Juan Carlos; Novo Rodríguez, Jesús Manuel; Bóveda Fontán, Julia; Martín Alvarez, Remedios; Prados Castillejo, Jose Antonio; Rivas Doutreleau, Gabriela Renée; Domingo Peña, Carmen; Castro Moreno, Jaime Jesús; et al.
Abstract: Background: Motivational interviewing (MI) is a collaborative, goal-oriented method to help patients change behaviour. Tools that are often used to measure MI are the motivational interviewing skills code' (MISC), the 'motivational interviewing treatment integrity' (MITI) and the 'behaviour change counselling index' (BECCI). The first two instruments have not been designed to be used in primary healthcare (PHC) settings. The BECCI actually is time-consuming. The motivational interviewing assessment scale (MIAS, 'EVEM' in Spanish) was developed to measure MI in PHC encounters as an alternative to the previous instruments. Objectives: To validate MIAS as an instrument to assess the quality of MI in PHC settings. Methods: (a) Development: Sixteen experts in MI participated in the design, face and consensus validity, using a Delphi-type methodology. (b) Validation: Setting: 27 PHC centres located in Spain. Subjects: four experts in MI tested its psychometric properties with 332 video recordings coming from the Dislip-EM study (consultations provided by 37 practitioners). Measurements: dimensionality, internal consistency, reliability (intra-class correlation coefficient—ICC), sensitivity to change and convergent validity with the BECCI scale. Results: A 14-item scale was obtained after the validation process. Factor analysis: two factors explained 76.6% of the total variance. Internal consistency, α = 0.99. Reliability: intra-rater ICC = 0.96; inter-rater ICC = 0.97. Sensitivity to change: means before and after training were 23.63 versus 38.57 ( P < 0.001). Spearman's coefficient between the MIAS and the BECCI scale was 0.98 ( P < 0.001). Conclusion: The MIAS is a consistent and reliable instrument to assess the use of MI in PHC settings.